2022
DOI: 10.1073/pnas.2205043119
|View full text |Cite
|
Sign up to set email alerts
|

Crystallography of honeycomb formation under geometric frustration

Abstract: As honeybees build their nests in preexisting tree cavities, they must deal with the presence of geometric constraints, resulting in nonregular hexagons and topological defects in the comb. In this work, we study how bees adapt to their environment in order to regulate the comb structure. Specifically, we identify the irregularities in honeycomb structure in the presence of various geometric frustrations. We 3D-print experimental frames with a variety of constraints imposed on the imprinted foundations. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
(46 reference statements)
1
5
0
Order By: Relevance
“…Furthermore, we would expect 5-7-sided cell pairs where the 5-sided cell is a deformed worker cell and the 7-sided cell is a deformed reproductive cell. This agrees with current and previous observations [ 7 , 30 ].…”
Section: Methodssupporting
confidence: 94%
See 3 more Smart Citations
“…Furthermore, we would expect 5-7-sided cell pairs where the 5-sided cell is a deformed worker cell and the 7-sided cell is a deformed reproductive cell. This agrees with current and previous observations [ 7 , 30 ].…”
Section: Methodssupporting
confidence: 94%
“…To relate the cell center representation to cells, we use the centers to generate a Voronoi partition to decompose the plane into polygonal areas, i.e., polygons that have the properties that all the points inside a polygon are closest to the cell center that is inside the partition, and all the edges are equidistant from 2 cell centers. Prior studies on irregular nest construction found that the Voronoi partition generated by cell centers is in good agreement to the observed cell walls [30]. To derive a bound on the number of necessary non-hexagonal cells, we use the fact that the graph generated by connecting centers whose Voronoi partition polygons share an edge is a Delaunay triangulation, i.e., a graph where any circumscribing circle of a triangle contains no other vertices.…”
Section: Geometric Model For Non-uniform Hexagonal Lattice Structurementioning
confidence: 86%
See 2 more Smart Citations
“…at the boundaries, while conforming to the space and resources available (13). The resulting structure inevitably contains non-regular hexagons and topological defects with various cell sizes, to adapt to environmental constraints (14)(15)(16)(17). Adjusting the sizes of hexagons during honeycomb construction may serve additional purposes, often dictated by the colony's requirements.…”
Section: Introductionmentioning
confidence: 99%